So much to do and so little time: Effort and perceived temporal distance - Gabriela Jiga-Boy (Psychological Science, 2010)
In a series of five experiments, we showed that the perception of temporal distance to a future event is shaped by the effort one must invest to realize the event. Studies 1a and 1b showed that when actors are faced with realizing an event by a certain deadline, more effortful events are perceived as closer in time, regardless of the objective temporal distance to the deadline. This negative relationship was reversed, however, when deadlines were absent (Study 2). Finally, priming high effort reduced perceived temporal distance to an event, whereas priming low effort increased perceived temporal distance to the event (Studies 3 and 4). The implications of these findings for models of temporal distance are discussed.